ANALISIS RISIKO KESELAMATAN DAN KESEHATAN KERJA PADA PROSES BUNKERING KAPAL MENGGUNAKAN METODE HIRADC DAN FTA - Muhammad Asyrof Faruq Qushoyyi (2023)
PT. KBS is a company that operates as a port service. The work problem at PT. KBS, work accidents occur in the construction sector which can cause physical damage to the workers' body parts and reduce labor productivity. To reduce the causes of work accidents in the Ship Bunkering section, an evaluation is carried out in identifying hazards and dealing with the causes of work accidents. Identification of the potential (source) of this hazard is done by recording all the steps for each activity that occurs in the Ship Bunkering Division at PT. KBS uses a risk management stage approach or Hazard Identification, Risk Assessment, Determining Control (HIRADC) so that a total of 20 risk events are obtained. Potential hazards that have the highest Risk Priority Index (RPI) category have 3 risk events, then 17 high risk events to find the cause of risk events with Fault Tree Analysis. Recommendations according to potential hazards are to design a prototype overload warning system, use personal protective equipment (PPE), supervise the implementation of work activities, train and carry out routine inspections. So that the results obtained from the causes of work accidents are expected to reduce the level of work accidents that exist from previous accidents by using the HIRADC and FTA methods.